Sub-Saharan African Science, Technology, Engineering, and Mathematics Research : A Decade of Development - Blom, Andreas (Washington, DC: World Bank, 2015)
This book analyzes Africa's current performance in Science, Technology, Engineering and Math (STEM) research, as well as future trends. It looks at Africa's research performance over a decade, what it means for the continent's development and how it can benefit the growing number of young people who leave university each year looking for jobs.